Characterizing spatial differences between SPECT-ventilation and SPECT-perfusion in patients with lung cancer undergoing radiotherapy. (July 2021) - Forghani, Farnoush; Patton, Taylor; Kwak, Jennifer; Thomas, David; Diot, Quentin; Rusthoven, Chad; Castillo, Richard; Castillo, Edward; Grills, Inga; Guerrero, Thomas; Miften, Moyed; Vinogradskiy, Yevgeniy
Abstract: This study investigates agreement between ventilation and perfusion for lung cancer patients undergoing radiotherapy. Ventilation-perfusion scans of nineteen patients with stage III lung cancer from a prospective protocol were compared using voxel-wise Spearman correlation-coefficients. The presented results show in about 25% of patients, ventilation and perfusion exhibit lower agreement.